Involvement of the GABAergic septo-hippocampal pathway in brain stimulation reward. - Germán Vega-Flores; Agnès Gruart; José M Delgado-García (PLoS ONE, 2014)
The hippocampus is a structure related to several cognitive processes, but not very much is known about its putative involvement in positive reinforcement. In its turn, the septum has been related to instrumental brain stimulation reward (BSR) by its electrical stimulation with trains of pulses. Although the anatomical relationships of the septo-hippocampal pathway are well established, the functional relationship between these structures during rewarding behaviors remains poorly understood. To explore hippocampal mechanisms involved in BSR, CA3-evoked field excitatory and inhibitory postsynaptic potentials (fEPSPs, fIPSPs) were recorded in the CA1 area during BSR in alert behaving mice. The synaptic efficiency was determined from changes in fEPSP and fIPSP amplitudes across the learning of a BSR task. The successive BSR sessions evoked a progressive increase of the performance in inverse relationship with a decrease in the amplitude of fEPSPs, but not of fIPSPs. Additionally, we evaluated CA1 local field potentials (LFPs) during a preference task, comparing 8-, 20-, and 100-Hz trains of septal BSR. We corroborate a clear preference for BSR at 100 Hz (in comparison with BSR at 20 Hz or 8 Hz), in parallel with an increase in the spectral power of the low theta band, and a decrease in the gamma. These results were replicated by intrahippocampal injections of a GABAB antagonist. Thus, the GABAergic septo-hippocampal pathway seems to carry information involved in the encoding of reward properties, where GABAB receptors seem to play a key role. With regard to the dorsal hippocampus, fEPSPs evoked at the CA3-CA1 synapse seem to reflect the BSR learning process, while hippocampal rhythmic activities are more related to reward properties.